Assessing the potential cost of a failed Doha Round - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2017)
The goal of this chapter is not to uncover additional benefits associated with the DDA, but to reexamine the value of an agreement by considering potential gains and losses in a moving landscape of trade policies. Traditional impact studies have assessed the potential gains of the Doha negotiations by comparing the consequences of the negotiation modalities to the status quo baseline. Therefore, the cost of failed negotiations has been seen as just an opportunity cost representing the unrealized gains. This approach, however, may have underestimated the real costs associated with the failure of the DDA. Such a drastic event would make the business-as-usual scenario uncertain because the status quo is not a long-term perspective for trade policies. The current trend of multilateral trade liberalization may not survive this failure, and the global public good provided by the WTO that helps to free trade in a stable and less-distorted environment may vanish. Therefore this chapter compares the effects of a DDA scenario with other relevant alternatives.